Life Accentuation in Cognitive Dissonance and Hedonistic Behavior between Jakarta and Moscow Adolescents - Kuswanti, Ana; Muzykant, Valerii L.; Moenawar, Mohamad Ghozali; Maryam, Siti; Zempi, Charun Nisa; Tayibnapis, Radita Gora; Santoso, Hudi (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2024)
Information and communication technology play an important role in the development of communication, one of which is the utilization of the online shop platform, to fulfill the desire for a hedonistic lifestyle. The changes in lifestyle focus on seeking unlimited pleasure and satisfaction. Life accentuation assumes that a person will feel happy by seeking happiness and avoiding feelings of pain, disappointment, and sadness. The research objective was to compare Jakarta and Moscow adolescents' cognitive dissonance and hedonism behavior. The comparative descriptive quantitative research method was used on 101 Moscow teenage respondents and 102 Jakarta respondents using cognitive dissonance theory and behavioral theory. The results were (1) ‘Looking for unlimited pleasure and satisfaction’ is ‘often’ (54.10%) by Jakarta teenagers, higher than Moscow teenagers (only 39.40%), and ‘sometimes’ (52.10%). (2) The dimension of ‘seeking as much happiness as possible and avoiding painful feelings’, Jakarta teenagers are 45.90% while Moscow teenagers are 36.60%, and ‘sometimes’ (56.30%). (3). For the dimensions of ‘seeking happiness symbolically’, Jakarta teenagers are more ‘often’ (53.10%) than Moscow teenagers (36.60%) and ‘sometimes’ (52.10%). (4) In the dimension of ‘pleasure is the most important thing in life’ there are differences between teenagers in Moscow and teenagers in Jakarta (54.10%) and Moscow teenagers are ‘often’ (63.40%) lower and ‘sometimes’ tend to behave hedonistically (63.40%).